Evaluating the spatial distribution of soil physicochemical characteristics and heavy metal toxicity potential in sediments of Nworie river micro-watershed Imo state, southeastern Nigeria - Ubuoh Emmanuel Attah (KeAi Communications Co., Ltd., 2021)
Understanding soil properties, characteristics and their variation is important for their sustainable utilization and proper management of soil and micro-watershed. Sediments can act as reservoir for heavy metals, thereby they are used to assess the pollution status of the rivers. Therefore, the study aimed to evaluate the spatial distribution of soil physicochemical characteristics and heavy metal toxicity potential in sediments of Nworie river micro-watershed Imo state, Southeastern, Nigeria. . The sediments of Nworie river micro-watershed were from three different locations. The first location is at Egbeada Village, second is at Amakohia- Egbeada Road and the third location is behind Umuzuruike Hospital Owerri, designated as station one, station two and station three respectively. The physiochemical properties of sediments examined were sand, silt, clay, texture, pH, phosphorous Nitrogen, Organic carbon, organic matter, calcium, magnesium, potassium, sodium, ECEC, and base saturation. The results showed that the textural class of sediment was sandy. The pH of the sediments was found to be acidic and was not within the WHO limit. Results also showed that, sediments had a low exchangeable base. The heavy metals were lowly present in sediments. However, cadmium recorded a higher concentration than the other heavy metals. The contamination factor of Cr, Cu, Pb, and Zn were less than zero at the three course streams indicating that sediments of the Nworie River was lowly contaminated with Cr, Cu, Pb, and Zn. The pollution load values were observed to be less than one (1) indicates no pollution. Appropriate measures should be taken to avert anthropogenic sources that degrade Nworie River Micro-Watershed.